INDUCED BREAST CANCER MCF-7 CELLS APOPTOSIS FROM EXTRACT COMBINATION OF JENGKOL PODS (Archidendron jiringa) AND PETAI CINA LEAVES (Leucaena leucocephala) - Harry Noviardi; Sitaresmi Yuningtyas; Lydia Agustin (Jurnal Farmasi Sains dan Praktis, 2020)
The jengkol pod exocarp and petai cina leaves potentially as breast anticancer due to its highly toxic. The activity of cytotoxicity to the MCF-7 cells by the combination of jengkol pod exocarp and petai cina leaves is included in the potential category. The research aimed to determine the influence of the combination of jengkol pod exocarp and petai cina leaves on induction of the MCF-7 breast cancer apoptosis. Induction cell apoptosis of MCF-7 from a combination of extracts by using a double staining method. The cytotoxicity test from the extract combination of jengkol pod exocarp and petai cina leaves was determined by the MTT method. The extracts were made by comparing the mass of jengkol pod exocarp and petai cina leaves with comparisons of 5:1, 7:1, and 9:1. The IC50 values of the combination of jengkol pod exocarp and petai cina leave the ratio of 5:1, 7:1, and 9:1 were 11.7; 7.5; and 1.9 ppm, respectively. Apoptosis activity of the extract combination of the double staining test results showed MCF-7 cells experiencing orange and bright green fluorescence. The cellular form becomes wrinkled from the initial condition of the cell. Based on the results of the study showed a combination of jengkol pod exocarp and petai cina leaves could induce the MCF-7 breast cancer apoptosis cell.